Cross-Layer arrangement for Wireless Mesh Networks - Sangeetha, P; Mala, R (International Journal of Computer Sciences and Engineering, 2014)
Cross-Layer arrangement has lately grow the new hype in wireless communication systems. Cross-layer arrangement has a countless possible in upcoming wireless communication Systems. Cross-layer arrangement for excellence of facility (QoS) in wireless mesh networks (WMNs) has complicated abundant investigation attention recently. Numerous key machineries spanning all layers, after bodily up to network layer, consume to be browbeaten and unique procedures for harmonic and well-organized layer communication necessity be designed.